Generalized difference sequence spaces and their dual spaces - Bektas, ÇA; Et, M; Colak, R (Academic Press Inc Elsevier Science, 2004)
The definition of the palpha-, pbeta- and pgamma-duals of a sequence space was defined by Et [Internat. J. Math. Math. Sci. 24 (2000) 785-7911. In this paper we compute palpha- and N-duals of the sequence V spaces Delta(m)(v) (X) for X = linfinity, c and c(0), and compute beta- and gamma-duals of the sequence spaces Delta(v)(m) (X) V for X = linfinity, c and c(0). (C) 2004 Elsevier Inc. All rights reserved.
Keywords: difference sequence spaces; N-dual; p alpha-; p beta- and p gamma-duals